Determinants of outcomes in patients with hepatitis B virus-decompensated cirrhosis - Yi-Jie Huang; Jun-Sing Wang; Cheng-Hsu Chen; Shou-Wu Lee; Chung-Hsin Chang; Szu-Chia Liao; Yen-Chun Peng; Teng-Yu Lee; Tsai-Chung Li (Scientific Reports)
Abstract The role of pre-treatment HBV DNA levels on the prognosis of hepatitis B virus-related decompensated cirrhosis is unclear. This study investigated the effects of pre-treatment HBV DNA and other determinants on short-term and long-term survival of chronic hepatitis B (CHB) patients with decompensated cirrhosis. A total of 278 cirrhotic decompensated CHB patients treated with entecavir or tenofovir disoproxil fumarate were retrospectively enrolled. Cox regression models were used to analyze factors associated with all-cause mortality. The median follow-up time was 17 months (IQR2.17–58.94), during which 132 patients (47.4%) either died or underwent liver transplantation. The cumulative incidence of all-cause mortality was 16%, 29%, 34%, 39%, and 51% at the 1-month, 3-month, 6-month, 1-year, and 5-year follow-ups, respectively. Risk factors associated with 3-month all-cause mortality were age, presence of ascites and hepatic encephalopathy, baseline hepatitis flares, pre-treatment HBV DNA levels, and MELD scores. In the subgroup analysis, for 3-month all-cause mortality, significant associations of age, baseline hepatitis flares, and MELD scores with pre-treatment HBV DNA levels were observed (p for interaction were 0.005, 0.032, and 0.030, respectively). Risk factors associated with 5-year all-cause mortality were age, the presence of ascites and hepatic encephalopathy, and MELD scores. Liver functional reserve and age played a critical role in the prognosis of CHB patients with decompensated cirrhosis. Pre-treatment HBV DNA levels had an impact on short-term all-cause mortality, but not on long-term all-cause mortality.